PREVALENCE OF GASTROINTESTINAL PARASITES AND CONDITION FACTOR OF AUCHENOGLANIS BISCUTATUS (GEOFFREY ST. HILARIE, 1827) IN KIRI RESERVOIR, SHELLENG, ADAMAWA STATE, NIGERIA. (FUDMA JOURNAL OF SCIENCES, 2023)
The present study was designed to investigate the prevalence of gastrointestinal parasitic infection in Auchenoglanis biscutatus in Kiri reservoir, Shelleng, Adamawa State. Auchenoglanis biscutatus species were randomly sampled every month for a period of six months from May to October, 2017. Each specimen was dissected and the dissected fish intestine including the stomach was open up by means of a pair of dissecting scissors and placed in a Petri dish, dissecting microscope was used to check for the presence of parasites, identification keys was used to identify those parasites found, Chi square was used to show the prevalence of parasites in relation to sex, length and weight. The distribution of infected Auchenoglanis biscutatus showed an overall prevalence of 36 (46.75%), the prevalence in relation to sex showed that the Males had a prevalence rate of 20 (55.66%), while Females had 16 (39.02%) prevalence rate. The distribution of parasite species showed that male had 26 (50.98%) Posthodiplostomulum minimum metacercaria and 10 (52.17%) Myxobolus sp. with parasite load of 36, while the females had 25 (49.02%) Posthodiplostomulum minimum metacercaria and 8 (44.44%) Myxobolus sp, with a parasite load of 33. There is significant association between parasite infection and sex at p > 0.05. There is occurrence of gastrointestinal parasites in Auchenoglanis biscutatus found in Kiri reservoir, and thus good culinary practices should be adopted to decimate risks to public health
Keywords: Gastrointestinal Parasites, Auchenoglanis biscutatus, Condition Factor, Kiri Reservoir, Shelleng